2022
DOI: 10.18502/fid.v19i26.10597
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Heating of Low-Shrinkage Composite Resins: Effects on Color Stability and Surface Roughness

Abstract: Objectives: The present study aimed to investigate the effect of preheating on the color stability and surface roughness of a silorane-based composite resin. Materials and Methods: A total of 44 Filtek P90 composite resin disks, (10mm×1mm), were fabricated using plastic molds and were divided into two groups. In group 2, the composite resin syringes were placed in a thermostatically controlled water bath at 55‒60°C before preparing the disks. After polishing the samples with silicon carbide papers, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…23 Oskoee et al found an increase in the roughness values of micro hybrid-based composite resins that were preheated, which contradicts these studies. 24 Thus, the goal of this study is to assess how heating the fluoride varnish material affects its roughness. Bacterial uptake of restorative materials is directly correlated with their surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…23 Oskoee et al found an increase in the roughness values of micro hybrid-based composite resins that were preheated, which contradicts these studies. 24 Thus, the goal of this study is to assess how heating the fluoride varnish material affects its roughness. Bacterial uptake of restorative materials is directly correlated with their surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the second null hypothesis of this study was rejected. The discoloration exhibited by a material has been shown to be either directly or indirectly related to the surface roughness of the material [35,36]. Chowdhury et al [37] reported that, as the surface roughness increased, the discoloration also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that coffee is the most frequently applied solution for coloring resin composites [21,[39][40][41][42]. Discoloration, which mostly occurs due to the adsorption and absorption of exogenous pigments, is an important and influential factor of the color instability of restorations [35]. Coffee solutions have yellow pigments of different polarities.…”
Section: Discussionmentioning
confidence: 99%